Pengaruh Karakteristik Individu Dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) Pendamping PKH Dengan Komitmen Organisasi Sebagai Variabel Intervening - Ismuhadi (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to examine the influence of individual characteristics and job satisfaction on organizational commitment, the influence of individual characteristics, job satisfaction and organizational commitment to OCB, as well as the role of organizational commitment as intervening variable whether to mediate the relationship of individual characteristics and job satisfaction to OCB nurses. Data analysis method used in this research is structural equation modeling model, sampling technique with gtotal sampling method, with total sample 103. The results of his research that the influence of individual characteristics have a positive and insignificant effect on organizational commitment. job satisfaction has a positive but insignificant effect on organizational commitment. individual characteristics have a positive and significant effect on OCB. job satisfaction has a positive and significant effect on OCB. The organizational commitment has a positive and significant impact on OCB. The role of organizational commitment as an intervening variable does not mediate the relationship of individual characteristics and job satisfaction to OCB.